Revision of the Ambrysus guttatipennis Stål species complex (Heteroptera: Naucoridae: Cryphocricinae) with the descriptions of six new species from Mexico - Reynoso-Velasco, Daniel; Sites, Robert W. (Zootaxa, 2016)
The Ambrysus guttatipennis Stål species complex is revised and includes A. arizonus La Rivers, A. bispinus La Rivers, A. drakei La Rivers, A. guttatipennis Stål, A. mexicanus Montandon, and A. mormon Montandon. Six new species that belong to this complex are described from Mexico: A. ayoyolin n. sp., A. bowlesi n. sp., A. contrerasi n. sp., A. itsipatsari n. sp., A. noveloi n. sp., and A. veracruzanus n. sp. The subspecies A. mormon australis La Rivers, A. m. heidemanni Montandon, and A. m. minor La Rivers are proposed as junior synonyms of A. m. mormon Montandon. A supplemental redescription of A. guttatipennis Stål based on the holotype is provided and a lectotype of A. mexicanus Montandon is designated. Ambrysus arizonus is newly recorded from Mexico and A. bispinus from Guatemala. Most of the species in this complex occur only in Mexico, although A. arizonus and A. mormon are distributed in Mexico and the United States, and A. bispinus is distributed in Mexico and Guatemala. Ambrysus mormon has the widest distribution of any species in this complex. Features uniting these species are related to male genitalia and structures associated with male and female genitalia.